4-Ferrocenylaniline-based ROS-responsive prodrugs with anticancer activity - Xu, Honggui; Annamadov, Saparmyrat; Mokhir, Andriy (Journal of Organometallic Chemistry, 2022)
Ferrocene derivatives often exhibit anticancer activity. For example, our group has developed aminoferrocene-based (AF) prodrugs, which are activated in the presence of reactive oxygen species (ROS), present in large quantities in cancer cells. The activation reaction leads to formation of AF's, whose redox potential is shifted by 300–400 mV to negative values as compared to the parent AF prodrugs. Correspondingly, these drugs are very electron rich and can, therefore, act as catalysts of generation of highly toxic hydroxyl radicals (HO●) from H2O2. That contributes to the cytotoxicity of AF prodrugs. Unfortunately, AF's are chemically very unstable. Therefore, their lifetime in cells is < 1 h that limits the anticancer activity of the AF prodrugs. In this paper we report on new 4-ferrocenylaniline-based (4-FcAn) prodrugs. These are activated in the presence of ROS thereby releasing 4-FcAn. We confirmed that 4-FcAn is more electron rich than the corresponding prodrug (ΔE1/2 = 86 mV) and can generate HO● from H2O2 analogously to AF. Furthermore, we observed that (a) 4-ferrocenylanilines are substantially more stable (>6 h) than AF's and (b) the corresponding prodrugs are substantially more active than the structurally related AF prodrugs. We found that, analogously to AF prodrugs, the new prodrugs exhibit their anticancer activity via generation of ROS in cancer cells.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Anticancer; Ferrocene; Prodrug; Reactive oxygen species; Redox catalysis

An Endoplasmic Reticulum Specific Pro-amplifier of Reactive Oxygen Species in Cancer Cells - Xu, Honggui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al. (Angewandte Chemie International Edition, 2021)
The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER-targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N-alkylaminoferrocene-based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth-Kellner lymphoma (NK/Ly) murine model.
CRIS-Team WoS Importer:2021-04-16

Anticancer Aminoferrocene Derivatives Inducing Production of Mitochondrial Reactive Oxygen Species - Özkan, Hülya Gizem; Thakor, Vanrajsinh; Xu, Honggui; Bila, Galyna; Bilyy, Rostyslav; Bida, Daria; Boettcher, Martin; Mougiakakos, Dimitrios; Tietze, Rainer; Mokhir, Andriy (Chemistry - A European Journal, 2022)
Elevated levels of reactive oxygen species (ROS) and deficient mitochondria are two weak points of cancer cells. Their simultaneous targeting is a valid therapeutic strategy to design highly potent anticancer drugs. The remaining challenge is to limit the drug effects to cancer cells without affecting normal ones. We have previously developed three aminoferrocene (AF)-based derivatives, which are activated in the presence of elevated levels of ROS present in cancer cells with formation of electron-rich compounds able to generate ROS and reduce mitochondrial membrane potential (MMP). All of them exhibit important drawbacks including either low efficacy or high unspecific toxicity that prevents their application in vivo up to date. Herein we describe unusual AF-derivatives lacking these drawbacks. These compounds act via an alternative mechanism: they are chemically stable in the presence of ROS, generate mitochondrial ROS in cancer cells, but not normal cells and exhibit anticancer effect in vivo.
CRIS-Team WoS Importer:2022-04-29

Hybrids of a 9-anthracenyl moiety and fluorescein as chemodosimeters for the detection of singlet oxygen in live cells - Chercheja, Serghei; Daum, Steffen; Xu, Honggui; Beierlein, Frank; Mokhir, Andriy (Organic & Biomolecular Chemistry, 2019)
Singlet oxygen (1O2) plays an important role in human innate immune response, plant physiology and anticancer photodynamic therapy (PDT). Therefore, its monitoring by convenient and sensitive methods (e.g. by detecting a fluorescence signal) by using non-toxic reagents would be advantageous. Known fluorogenic 1O2-chemodosimeters can potentially consume reducing agents in cells leading to the generation of toxic side products that limit their applications. In this paper we report on a series of 9-anthracenyl-fluorescein hybrids, which do not require any reducing agents for their reaction with 1O2. The selected compound 8d at a very low concentration of 100 nM is able to detect 1O2 in live human promyelocytic leukemia HL-60 cells with over 35-fold fluorescence signal enhancement within only 20 min assay time. This chemodosimeter is not toxic to HL-60 cells at concentrations ≤1 μM (higher concentrations were not tested) even at long incubation times ≤48 h.
CRIS-Team Scopus Importer:2019-12-10

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Supramolecular Recognition of Cytidine Phosphate in Nucleotides and RNA Sequences - Morozov, Boris; Oshchepkov, Aleksandr S.; Klemt, Insa; Agafontsev, Aleksandr; Krishna, Swathi; Hampel, Frank; Xu, Honggui; Mokhir, Andriy; Guldi, Dirk Michael; Kataev, Evgeny (JACS Au, 2022)
Supramolecular recognition of nucleotides would enable manipulating crucial biochemical pathways like transcription and translation directly and with high precision. Therefore, it offers great promise in medicinal applications, not least in treating cancer or viral infections. This work presents a universal supramolecular approach to target nucleoside phosphates in nucleotides and RNA. The artificial active site in new receptors simultaneously realizes several binding and sensing mechanisms: encapsulation of a nucleobase via dispersion and hydrogen bonding interactions, recognition of the phosphate residue, and a self-reporting feature─“turn-on” fluorescence. Key to the high selectivity is the conscious separation of phosphate- and nucleobase-binding sites by introducing specific spacers in the receptor structure. We have tuned the spacers to achieve high binding affinity and selectivity for cytidine 5′ triphosphate coupled to a record 60-fold fluorescence enhancement. The resulting structures are also the first functional models of poly(rC)-binding protein coordinating specifically to C-rich RNA oligomers, e.g., the 5′-AUCCC(C/U) sequence present in poliovirus type 1 and the human transcriptome. The receptors bind to RNA in human ovarian cells A2780, causing strong cytotoxicity at 800 nM. The performance, self-reporting property, and tunability of our approach open up a promising and unique avenue for sequence-specific RNA binding in cells by using low-molecular-weight artificial receptors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cytosine; encapsulation; fluorescence sensing; nucleotide recognition; synthetic receptors